Cracks in the wall: Entrepreneurial action theory and the weakening presumption of intended rationality - Hunt, Richard A.; Lerner, Daniel A.; Johnson, Sheri L.; Badal, Sangeeta; Freeman, Michael A. (Journal of Business Venturing, 2022)
Entrepreneurship scholarship finds itself in something of a quandary concerning rationality. While an increasingly large body of empirical work has found evidence of less-deliberative and even impulsive drivers of business venturing, the dominant theories of entrepreneurial action remain anchored to the assumption that intended rationality is a defining attribute of entrepreneurship. The growing schism between entrepreneurial action theory (EAT) on the one hand, and empirics and practice on the other hand, represents a consequential and exciting opportunity for the field to revisit its core assumptions regarding rationality, particularly the presence, role, and function of rational intentionality. In this study, we undertake a review and exploratory investigation of the assertion that without reasoned intentionality there is no entrepreneurship. Our work generates three important insights that contribute to rethinking key facets of the most prominent and influential EATs: alternative, non-rational pathways to business venturing exist with a non-ignorable prevalence; a proclivity towards reasoned intentionality is not invariably prescriptive; and, less-reasoned, less-deliberative tendencies do not constitute an entrepreneurial death sentence. Rather, entrepreneurs (including highly successful ones) embody a shifting blend of rational and non-rational proclivities, motivations, decisions, and actions.